Time efficiency of a web-based questionnaire in urogynecology: a randomized study. Issue 4 (April 2016) - Posthuma, Selina; Ploeg, J.; Etten-deBruijn, Britt; Ham, David
Abstract Introduction and hypothesis Based on nationwide recommended questionnaires for women with pelvic floor dysfunction (PFD), we developed a web-based questionnaire (WBQ) that can be sent to women prior to their first visit. We hypothesized that using this WBQ would contribute to a more efficient first visit. Furthermore, we were interested in the satisfaction of patients who used the WBQ. Methods Women referred for PFD were randomized between WBQ and no questionnaire. Time spent per consultation was recorded in total and in split times for history taking, physical examination, counseling, and administration. Patient experience was evaluated by a standardized telephone interview. Results One hundred and twenty-eight women were randomized: 64 in the WBQ group and 64 in the control group. History taking was significantly shorter in the WBQ group [mean difference (MD) −1 m 32 s; 95 % confidence interval (CI) −2:41 to −0:23], and time for counseling was significantly longer (MD 1 m 21 s; 95 % CI 0:06–2:37). Overall time of the consultation was equal. The need for an additional visit tended to be less frequent in the WBQ group [53 % versus 64 %; relative risk (RR) 1.3, 95 % CI 0.8–2.0]. Forty-nine percent of women considered the WBQ time consuming without adding value. Conclusions The WBQ contributed to a slightly more efficient use of the first consultation. While differences were small and patient satisfaction was low, other benefits of the WBQ should define whether the WBQ will be introduced.